Sustainable Energy Outlook: Biodiesel from Used Cooking Oil in Palestine - Ahmad Ashqar; Fihme Hantoli; Maher Abdulkareem; Ihab H. Alsurakji (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Developing alternatives to fossil fuels has become increasingly essential due to the ongoing depletion of non-renewable energy sources worldwide. Biodiesel, a promising substitute for fossil fuels, is not only environmentally friendly but also compatible with diesel engines. The process of converting used vegetable oils or animal fats into biodiesel is known as transesterification. In order to increase Palestine's potential for renewable energy and attain energy independence, biodiesel could be used as a renewable resource. This study focuses on the viability of developing a home appliance that can transform used cooking oil into biodiesel appropriate for domestic usage. Currently, used cooking oil is disposed of inappropriately in Palestine, causing serious environmental harm. Palestine stands to gain by addressing this environmental problem and making it simpler to use used cooking oil as a renewable energy source. Therefore, the main objective of this study is to create a machine that is simple to operate, affordable in comparison to other devices on the market, and needs minimal maintenance. An in-house prototype was built at An-Najah National University's workshop for 4,500 NIS (or roughly $1,320). In addition, a number of lab tests were performed to assess the characteristics of the cooking oil and the required reaction conditions, such as temperature, mixing rate, and the right catalyst. According to the findings, the created machine has a production cost that is 25% lower than that of conventional diesel while maintaining a comparable level of performance in diesel engines. This study opens the door for a long-term solution to Palestine's energy problems and environmental problems.